Pecu: a multicenter study on pediatric patients with cold-induced urticaria - Karaaslan, H. B. Gemici; Soyoz, O.; Celik, F. Celebi; Akbas, H.; Karagol, H. I. Ertoy; Aksoydan, B. C.; Kiykim, A. (Wiley, 2025)
[Abstract Not Available]
European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) Congress -- JUN 13-16, 2025 -- Glasgow, SCOTLAND